Activities of Chalcone Derivatives from Boesenbergia rotunda Against Human Estrogen Receptor Alpha of Breast Cancer by In Silico - Maria Claudya; Dini Kesuma; Aguslina Kirtishanti; I Gede Ari Sumartha; Marsha Anggita Amelia (Jurnal Penelitian Pendidikan IPA, 2024)
The high prevalence of cancer must be overcome with prompt and appropriate prevention and treatment. New drug design is an effort to develop existing drugs, and their molecular structure and biological activity have been known through structural modification. It encourages researchers to explore Indonesia's natural resources, especially plants with anticancer activity, namely by synthesizing chalcone-derived compounds derived from the isolation of Fingerroot rhizomes (Boesenbergia rotunda). The most common flavonoid compound found in rhizomes fingerroot plants is pinostrobin. Pinostrobin compounds and their derivatives are synthesized, resulting in chalcone compounds and their derivative modifications. The author conducted an in-silico test on pinostrobin compounds and 19 of their derivatives, chalcone compounds, and 18 derivatives using estrogenic-a receptors with PDB codes 3ERD and 1G50. The author hoped that from this silico test, compounds with more potential as anticancer for breast cancer would be obtained based on the results of docking with 3ERD and 1G50 receptors and can then be synthesized. In the results of this study, the compounds Bis-4-bromobenzyoxychalcone and Bis-4-chlorobenzyloxychalcone are the most appropriate compounds to be synthesized. It is hoped that in the future, they can be continued with activity tests of these compounds, both in vitro and in vivo, because these compounds are predicted to have the best activity and do not have hepatotoxic or other toxicity effects